Chloroquine Treatment Suppresses Mucosal Inflammation in a Mouse Model of Eosinophilic Chronic Rhinosinusitis - Choi, Mi-Ra; Xu, Jun; Lee, Seulgi; Yeon, Sun-Hee; Park, Soo-Kyoung; Rha, Ki-Sang; Kim, Yong Min (Allergy, asthma & immunology research, 2020)
Purpose The Toll-like receptor 9 (TLR9) signaling pathway is involved in the pathogenesis of chronic rhinosinusitis (CRS) with nasal polyposis. The aim of this study was to assess the therapeutic potential of the TLR9 pathway inhibitor chloroquine in CRS mice. Methods The expression of type I interferons (IFNs) in human CRS tissues was evaluated using quantitative polymerase chain reaction (qPCR), western blotting, and immunofluorescence. Mice were divided into 4 treatment groups: the control, nasal polyp (NP), chloroquine treatment (NP + Chlq), and dexamethasone treatment (NP + Dexa) groups. The effects of chloroquine on polyp formation and mucosal inflammation were examined by hematoxylin and eosin staining. The expression levels of type I IFN, B-cell activating factor (BAFF), TLR9, high mobility group box 1 (HMGB1), and proinflammatory cytokine expression levels were assessed using qPCR, western blot, or enzyme-linked immunosorbent assay. Results IFN-α and IFN-β mRNA levels were significantly higher in patients with eosinophilic NPs (EPs) than in healthy individuals or non-EP patients. The polyp score, epithelial thickness, mucosal thickness, and the number of eosinophils in nasal mucosa were significantly higher in the NP group compared with the control, NP + Chlq, and NP + Dexa groups. NP + Chlq or NP + Dexa significantly suppressed the induction of type I IFN and BAFF expression in the NP group; these treatments also significantly suppressed the induction of TLR9, HMGB1, interferon regulatory factors, interleukin (IL)-6, IL-1β, tumor necrosis factor-α, and Th cytokine expression in the NP group. The secreted levels of anti-dsDNA Immunoglobulin G (IgG) were significantly higher in the NP group than in the control, NP + Chlq, and NP + Dexa groups. There were significant positive correlations between BAFF and mRNA levels of IFN-α/β/the protein levels of anti-dsDNA IgG. Conclusions Chloroquine may be used for the treatment of patients with eosinophilic CRS.